Do Declines in Bank Health Affect Borrowers’ Voluntary Disclosures? Evidence from International Propagation of Banking Shocks - LO, ALVIS K. (Journal of Accounting Research, 2014)
ABSTRACT I examine whether declines in banks’ financial health affect their borrowers’ disclosures. Prior studies indicate that, in relationship lending, banks and borrowers rely on private communication, rather than public disclosures, to resolve information asymmetries. When banking relationships are threatened, borrowers must turn to new funding sources, inducing them to reconsider their disclosure policies. This paper predicts that borrowers, whose banking relationships are threatened by declining bank health, change their public disclosures of forward‐looking information. Using the emerging‐market financial crises in the late 1990s as shocks to the health of certain U.S. banks, I find that affected banks’ U.S. borrowers increase both the quantity and informativeness of their management forecasts following these shocks compared to borrowers of unaffected banks. The results are similar using conference calls or the length of the Management's Discussion and Analysis section as alternative proxies for voluntary disclosure. Overall, these results provide new insights into the impact of availability of relationship lending on firms’ disclosure choices.